Apoptosis - Preedy, Victor R. (Series on modern insights into disease from molecules to man, 2010)
Covers Apoptosis from A to Z. This book explores a wide range of topics - from various cancers, asthma, and multiple sclerosis, to alcohol liver disease, chronic back pain, and cardiovascular health